Mandalika Special Economic Zone and the Potential for Regional Economic Development of Central Lombok Regency through Investment - Alfian Eikman Alfian; Sulhan Hadi; Ismail (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2022)
This study attempts to explain the various economic potentials created as a result of the domino effect of the development and development of the Mandalika Special Economic Zone in Central Lombok Regency, West Nusa Tenggara Province by mapping regional potentials whose development can be accelerated with capital assistance from foreign and domestic investment processes ( PMA and/or PMDN), which consists of data on several potential sectors that can be developed and built by expecting funding sources from investment or investment from outside. This study uses a qualitative approach with data collection methods using literature studies and interviews. The results show that there are several sectors that have the potential to support the development of the Mandalika Special Economic Zone in Central Lombok Regency. These sectors include tourism, agriculture, marine and fishing, where the agricultural, marine, and fishing sectors are the buffers of the tourism sector in the supply of raw materials for the food and beverage industry. The findings also explain that, although developing quite rapidly, tourism-supporting industries such as accommodation and F&B have not been able to meet the needs of the tourism sector in Central Lombok, so the potential for economic development is still very wide open. Therefore, the right strategy by utilizing economic network incentives from the existence of SEZs in attracting investment can be relied upon to accelerate the development of existing economic potential.